ORAL MELANOSIS: A CASE SERIES - Kumar, HARVINDER; CHATURVEDI, PANKAJ (Journal of Postgraduate Medical Institute, 2011)
There is very little information in literature about oral melanosis not associated with racial pigmentation or secondary to other syndromes. Various stimuli that can result in an increased production of melanin at the level of mucosa include trauma, hormones, radiation, and medications. Three such cases are reported in which stimulus for melanosis was mechanical trauma in form of smoking.